Comparative Study of the Performance of Breeds of Layers in Sub Sahara Region of Africa - Awobajo, O.K.; Salau, K.A.; Igbosanu, A.O.; Mako, A.A.; Ettu, R.O. (International Journal of Poultry Science, 2009)
The study was conducted to compare the performance of breeds of layers reared in Ogun State, with the view to identify the breeds of layers that perform well and to determine certain factors that can hinder the performance of layers. The state was divided into four divisions namely: Egba, Yewa/Awori, Ijebu and Remo. The information was collected by the use of structured questionnaire. These questionnaires were distributed to 120 farms in the state. i.e 30 questionnaires for each division. The data collected were analyzed using simple descriptive statistic and analysis of variance. The descriptive statistic shows certain factors that can affect the performance of layers. On the performance of breeds of layers, the result shows that there is high significant difference (P < 0.01) in the performance of breeds of layers in term of tolerant to heat stress, resistance to disease and production of more egg with less feed consumption. Also brown leghorn breed of layers was observed to be widely used by farmers across the state because of its higher performance compared to all other breeds reared in the state.